2017
DOI: 10.1007/s00404-017-4508-4
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary epidemiology and novel predictors of uterine rupture: a nationwide population-based study

Abstract: Despite policies implemented and changes in clinical practice, uterine rupture remains an important issue. Previously unidentified risk factors are playing now an important role, information that should be considered during patient counseling and clinical practice. Combinations of some of these factors may increase the risk of uterine rupture significantly enough to modify clinical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
15
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 29 publications
7
15
2
Order By: Relevance
“…In a large Norwegian register‐based study validated by review of medical records, the overall prevalence over 40 years was 1.3 (95% CI 1.2–1.5), increasing from 1.0 (95% CI 0.6–1.3) to 3.0 (95% CI 2.4–3.6) per 10 000 deliveries from the first to the last decade (2000–2008) . A large population‐based study in the USA reported a prevalence of 2.4 (95% CI 2.3–2.5) per 10 000 deliveries based on vital statistics data from 2011 to 2012 …”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…In a large Norwegian register‐based study validated by review of medical records, the overall prevalence over 40 years was 1.3 (95% CI 1.2–1.5), increasing from 1.0 (95% CI 0.6–1.3) to 3.0 (95% CI 2.4–3.6) per 10 000 deliveries from the first to the last decade (2000–2008) . A large population‐based study in the USA reported a prevalence of 2.4 (95% CI 2.3–2.5) per 10 000 deliveries based on vital statistics data from 2011 to 2012 …”
Section: Discussioncontrasting
confidence: 85%
“…4 A large population-based study in the USA reported a prevalence of 2.4 (95% CI 2.3-2.5) per 10 000 deliveries based on vital statistics data from 2011 to 2012. 5 We further explored the literature for population-based reports of uterine rupture in women with previous CS in high-income countries. Compared with three relatively large sources (Al-Zirqi et al, 4 Guise et al, 38 and Landon et al 7 ) reporting prevalences between 30 (95% CI 24-36) and 36 (95% CI 30-43) per 10 000 deliveries, 4,7,9 the prevalence in our study is lower, with a notably wide range between countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This systematic review and meta-analysis revealed that the prevalence of uterine rupture was 2% (95% CI: 1.99%, 3.01%) at national level. This was higher than findings of 40 Low and middle income countries (LMICs) review (1%) [ 44 ], nation-wide studies conducted in United Kingdom (0.2%) [ 45 ], United States (0.02%) [ 46 ], the Netherlands (0.059%) [ 12 ], WHO systematic review (0.31%) [ 5 ], Nigeria (1.2%) [ 47 ], Uganda (0.5%) [ 48 ] and 0.67% of uterine rupture in Senegal and Mali [ 49 ]. The possible difference might be due to the variation in population characteristics, setting and quality of health care service provision and utilization.…”
Section: Discussionmentioning
confidence: 66%
“…
Dear editors, I would like to thank Dr. Accordino and colleagues for their letter and interest in our study on contemporary epidemiology and novel predictors of uterine rupture [1]. I was pleased to read that Dr. Accordino and colleagues were able to identify the importance of the manuscript, as well as its implications on clinical practice.
…”
mentioning
confidence: 99%